Bending Strength Dependence of Fractoluminescence Intensity in Silica Glass, Single Crystal and Polycrystalline MgO - Tadashi Shiota (Japanese Society of Tribologists, 2008)
Fractoluminescence (FL) intensity and bending strength were simultaneously measured in silica glass, single crystal and polycrystalline MgO to study dependence of the FL on mechanical properties. In the silica glass, the FL intensity was positively correlated with the bending strength. Also, the positive correlation was found in the single crystal MgO. However, there was not clear dependence in the polycrystalline MgO. This suggests that the FL intensity is connected with the energy released by fracture in glasses and single crystal ceramics, and that grain boundary also contributes to the FL in polycrystalline ceramics.